2013
DOI: 10.1097/qai.0b013e318298a309
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Trends in Antiretroviral Usage and Drug Costs in HIV-Infected Children in Thailand

Abstract: Background As antiretroviral treatment (ART) programmes mature, data on drug utilization and costs are needed to assess durability of treatments and inform programme planning. Methods Children initiating ART were followed in an observational cohort in Thailand. Treatment histories from 1999–2009 were reviewed. Treatment changes were categorized as: drug substitution (within class), switch across drug class (non-nucleoside reverse-transcriptase inhibitors (NNRTIs) and protease-inhibitor (PI), and to salvage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…They do not reflect the overall costs for the implementation of early LPV/r-based ART, nor the long-term costs related to possible toxicity or poor adherence. However, our results are consistent with findings from other pediatric HIV treatment programs, again supporting the urgent need to increase access to ART the earliest possible [15,39–42]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They do not reflect the overall costs for the implementation of early LPV/r-based ART, nor the long-term costs related to possible toxicity or poor adherence. However, our results are consistent with findings from other pediatric HIV treatment programs, again supporting the urgent need to increase access to ART the earliest possible [15,39–42]. …”
Section: Discussionsupporting
confidence: 90%
“…These data, estimating patient costs of care will provide inputs for analyses modeling costs and cost-effectiveness of competing programmatic approaches [14,15]. This study assessed data on all costs of care in HIV-infected children during the first 12-months on LPV/r-based ART initiated before the age of 2 years, between 2011–2014, in Abidjan, Côte d’Ivoire.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients who switched to second-line therapy in our study, we found a median [IQR] time from VL rebound to switch of 4·9 months [1·7-13·4] which is comparable or slightly shorter than studies in resource limited settings 21,25 . When changing the VL rebound threshold to two consecutive viral load measurements above 1,000c/ml and 5,000c/ml, not surprisingly we found a higher estimated proportion of patients switching to second line therapy while the probability of resuppression without switch decreased with higher VL thresholds.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 79%
“…The median age, viral load, CD4 count, and CD4% at VL rebound were 10·6 years [5·6-13·4], 3·6 log 10 c/ml [3·1-4·2], 550 cells/μl , and 24% [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], respectively, and three-quarters of children initiated on a NNRTI-based regimen. Fifty one (30%) had already experienced some ART modifications not meeting the definition of switch prior to VL rebound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation